Book Review: Dancing at the River's Edge: A Patient and Her Doctor Negotiate Life with Chronic Illness - Brandon K. Attell (Journal of Public and Professional Sociology, 2014)
Review of the book Dancing at the River's Edge: A Patient and Her Doctor Negotiate Life with Chronic Illness, by Alida Brill and Michael D. Lockshin.